(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Abstract: Medical education is an emerging and essential discipline of medical science. It ensures quality education and training of medical students and doctors which will ultimately help in the best patient care. The clinicians who are involved in medical education face various problems and tension. There is need to explore these challenges and reasons behind these challenges. This study will explore the complex and multi-faceted challenges and reasons encountered by clinicians-educators. Methodology: A descriptive cross-sectional study was conducted at Post Graduate Medical Institute/ Lahore General hospital from April – June 2022. Total 50 participants were included in the current research who are medical educationist and Clinical educationist. respondents were of age group of 30 to 65 years including both male and female from all disciplines of medical colleges/universities. A self structured questionnaire was developed to collect data. Questionnaire have four domains (Time management, Economic burden. Social Life and rewards). Data was entered and analyzed by SPSS 25.0. All the qualitative variables were presented by frequency, percentages and graphs. Results: Total number of respondents 50. There were 35 males and 15 females. Majority (35) of the participants were 40-55yrs old. Experience as clinician medical educations varies among the participants from few months to 15 years. A significant portion of the participants (45) expressed challenges in managing time. Economic and financial obstacles were identified by 33 participants. Additionally, 31 participants indicated that they encounter social barriers, while 20 participants mentioned receiving rewards or privileges in their roles as medical educators. Those with up to 1 year of experience reported facing all the identified challenges, including difficulties with time management, economic constraints, social obstacles, and issues related to rewards.